Altruism as Component of Leadership: An Indian Perspective - Kaushal, Nidhi; Mishra, Sanjit (Journal of Entrepreneurship, Business and Economics, 2018)
Among various components of leadership, altruism has a significant place. Various noble characters around the world have exhibited the power of altruism in their behaviour which can be linked to their special achievements. Altruism is not very common among the entrepreneurs, and requires a strong willpower and determination with a selfless heart on the part of the subject. India’s ancient history and cultural accounts are full of stories through which relevant lessons in altruism can be profitably withdrawn. While performing and working with altruistic behaviour, a leader’s incredible approach of morality has been widely studied and examined in the Indian literary texts by several intellectuals. This paper intends to emphasise the significance of altruism in the modern competitive materialistic world. An attempt has been made to analyse the inevitability of altruism through the works of creative literature and their employability in the study of modern management.  Research paper Keywords: Leadership, Literature, Altruism, Ethics, Management, Noble Behaviour, Vedas  Reference to this paper should be made as follows: Kaushal, N., & Mishra, S. (2018). Altruism as component of leadership: An Indian Perspective, Journal of Entrepreneurship, Business and Economics , 6 (2), 1–11.